The Portrayal of Teacher’s Domination in Whiplash: (2014) the Movie - Muhammad Hisyam Rivai (Passage: Journal of English Language and Literature, 2023)
The study explores the teacher's domination in Whiplash film by utilizing power relation theory by Foucault (1995). Particularly, the study aims to examine the portrayal of domination in the teacher-student relationship. With regard to research design, this study employed a descriptive qualitative research design since the aim of the study is to explore a certain social phenomenon, which is the teacher’s domination in the film, entitled Whiplash. By using a close film's dialogue and character development analysis, segmentation of scenes was classified into parts of domination action in the movie. The findings of this study reveal that power relations are exercised through three stages of power domination: disciplinary, negotiation, and resistance. This finding shows us that power relations are all around us, from a minor scale of family, education, and politics. Overall, this study has shed light on the portrayal of teacher-student relationships in media and its potential impact on societal perceptions and expectations of these dynamics.